2013
DOI: 10.1016/j.jvs.2012.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the anatomic applicability of the multibranched endovascular repair of thoracoabdominal aortic aneurysm technique

Abstract: Most patients would have been suitable or could have been made suitable for a thoracoabdominal stent graft using current anatomic criteria. The applicability of MBEVAR will continue to change as the experience with the technique grows and devices evolve, as evidenced by the potential reduction in iliac bypasses after the introduction of a low-profile device and the ability to treat symptomatic or urgent patients with the off-the-shelf device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 19 publications
(26 reference statements)
4
71
1
Order By: Relevance
“…anatomical data presented in the current article support prior work showing that the distribution of branches on the t-branch stentgraft often matches the distribution of these arteries, 6,7 although it is possible that, in the case of the current study, patient selection may have played a role in eliminating outliers.…”
supporting
confidence: 78%
“…anatomical data presented in the current article support prior work showing that the distribution of branches on the t-branch stentgraft often matches the distribution of these arteries, 6,7 although it is possible that, in the case of the current study, patient selection may have played a role in eliminating outliers.…”
supporting
confidence: 78%
“…Gasper [6] and Bisdas [7] retrospectively assessed preoperative AngioCT of elective patients who underwent mbEVAR using CMD. Their relevant results showed that nearly two-thirds of patients (66% and 63%, respectively) where suitable to apply t-Branch, as the method of TAAA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…4). According to the instruction for use (IFU) and guidelines from previous studies [6,8], abovementioned conditions excluded patient from Zenith t-Branch usage. But taking into consideration high risk of the rupture, waiting for CMD was very hazardous option for this patient.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This time frame was not acceptable in urgent cases of symptomatic or ruptured aneurysms. The necessity for off-the-shelf mbSG led to the production of the Zenith t-Branch device (Cook Medical, Bloomington, IN, USA), which according to studies, could be a treatment solution for over twothirds of patients requiring a stent graft [2,3]. However, target artery cannulation and connection with the bridging stents can be challenging in unfavourable anatomy.…”
Section: Introductionmentioning
confidence: 99%